Analisis Guru untuk Meningkatkan Minat Belajar Siswa di Sekolah Dasar - Mila Amelia; Gusti Yarmi; Uswatun Hasanah (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2022)
The purpose of this study was to analyze the teacher's strategies in improving interest in learning in the first grade of SD Negeri Cipadu 01 Jalan Mutiara, No. 71, Cipadu Village, Larangan District, South Tangerang City. This research method is qualitative approach, with a descriptive approach. Based on the results of research on improving interest in learning in the first grade of SD Negeri Cipadu 01 by inviting students to make observations and discuss. Provide time for students to ask questions and provide opportunities for other students to answer these questions. Teachers also use a variety of learning media and evaluate theoretically and practically.